Fig. 14 in A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
Fig. 14. Arcticid bivalve?Arctica sp. from the upper Paleocene, Basilika Formation, Fossildalen, Spitsbergen, Svalbard. NRM-PZ Mo 149143, shell, left (A1) and right (A2) valves, dorsal (A3) and anterodorsal (A4) views, oblique dorsal view of left valve showing very fine commarginal ornament (A5). Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta Palaeontologica Polonica 64 (1) on page 119, DOI:10.4202/app.00554.2018, http://zenodo.org/record/10980900